PENYULUHAN STRATEGI PENGEMBANGAN USAHA MELALUI PEMANFAATAN LAHAN BAGI PETERNAK KAMBING DI KECAMATAN TOARI KABUPATEN KOLAKA - Purbaningsih, Yuli; Bahari, Doddy Ismunandar; Husnaeni, Husnaeni; Adi, Qadaruddin Fajri; Salam, La Ode Muh. Aswad; Jannah, Raodatul; Rahim, Abd.; Tatra, Afsitin Joan; Aminah, Aminah; Baba, Syahdar; Dagong, Muh. Ihsan A.; Nur, Aprisal (Indonesian Collaboration Journal of Community Services (ICJCS), 2024)
The community service program aims to increase the capacity of goat farming in Toari District, Kolaka Regency, with a focus on increasing farmers' knowledge and skills in livestock management. Through a series of ongoing training and mentoring activities, breeders are equipped with knowledge about livestock management, selecting superior seeds, feed management, livestock health care, financial management and marketing. Program implementation was carried out in an interactive and participatory manner, followed by regular assistance, which resulted in significant improvements in understanding, skills and welfare of farmers, as well as goat livestock productivity. In addition to providing individual benefits, the program also strengthens cross-sector collaboration, creating the potential to improve the overall sustainability of the goat farming sector in the region